I.v.21 Minutes - Labour Party (Ireland) (2008)
Minutes and supporting documentation of three meetings of the Management Committee which took place between 10 Jan 2008 – 29 Jan 2008. (66 pp)
Minutes and supporting documentation of six meetings of the Management Committee which took place between 5 Feb 2008 – 19 Mar 2008. (58 pp)
Minutes and supporting documentation of six meetings of the Management Committee which took place between 1 Apr 2008 – 13 May 2008. (40 pp)
Minutes and supporting documentation of four meetings of the Management Committee which took place between 20 May 2008 – 24 Jun 2008. (54 pp)
Minutes and supporting documentation of six meetings of the Management Committee which took place between 1 Jul 2008 – 23 Sept 2008. (60 pp)
Minutes and supporting documentation of five meeting of the Management Committee which took place between 30 Sept 2008 – 29 Oct 2008. Also includes ‘Financial Report to the Executive Management Committee’ prepared by Máire Whelan, National Treasurer, dated 17 Oct 2008. (69 pp) These materials are currently not available for consultation but this will be reviewed in 2027.
Minutes and supporting documentation of seven meetings of the Management Committee which took place between 4 Nov 2008 – 16 Dec 2008. (55 pp)
These materials are currently not available for consultation but this will be reviewed in 2027.